G51(P) Dermatitis artefacta: A difficult clinical problem. (7th April 2014) - Khan, MA; Ben-Zvi, G; Shaw, L; Glover, M; Bewley, A
Abstract : Introduction: The term dermatitis artefacta (DA) is used to refer to the skin manifestations of self-inflicted injury that is denied or not acknowledged by the patient. The presentation is variable but usually has some common findings. DA can be challenging to diagnose but even more difficult to manage. Patients are usually aware that their lesions are self-inflicted; however in rarer instances the activity may take place in a dissociated state outside the patient's awareness. DA in children is uncommon and very few published case series exist. To date, in children, the cause, treatment and prognosis are poorly understood. Aim: Our aim is to review the characteristics, management and outcomes of children with DA. Methods: We undertook a retrospective study of patients seen in the past 10 years. The diagnosis of DA was made from the clinical history and physical examination of skin lesions and on the basis of careful exclusion of organic disease. The criteria used to make the diagnosis of DA was based on uncharacteristic looking skin lesions on sites accessible to the patient, antecedent psychosocial events which may have precipitated the problem, and absence of alternative dermatological conditions to explain the lesions. Results: A total of 16 female patients were identified between 11–16 years. The anatomical sites affected included the face, arms, legs and abdomen. Types of skin lesions include superficial erosions, linear tears, blisters, petechiae, post-inflammatory pigmentation and scarring. The underlying psychological precipitants for DA were variable. Conclusion: Management of Patients with DA is difficult. A non-confrontational approach may be appropriate, as well as treating the involved skin lesions. In some cases, management involved excluding organic disease, engaging parents, where possible, without betraying the child's trust, identifying stressors, undertaking psychological counselling and being mindful of abuse. In other cases prompt explanation of the nature of the condition to the parents and the child was found to be the best approach. Outcomes were variable. A multidisciplinary approach is often required. Each patient must be treated on an individual basis. There are no national consensus guidelines. Clinicians are required to be alert to this rare but important condition.